Self-Efficacy in Sport - Research and strategies for working with athletes, teams, and coaches - Feltz, D. L.; Short,S.; Sullivan, P. (Human Kinetics, 2008)
Athletes, fans, coaches, and sport psychologists all know the power of self-efficacy in sport. With this new book, students, researchers, and practitioners now have a go-to reference on efficacy research packed with psychological strategies for helping athletes, teams, and coaches overcome specific weaknesses. Self-Efficacy in Sport—the first book devoted entirely to this important topic—compiles over 30 years of burgeoning self-efficacy research into a comprehensive and up-to-date analysis.